Tratamientos de superficies para pacientes con periimplantitis: Revisión de literatura crítica. (2021)
Peri-implant disease is an inflammatory process that affects the tissues around the implant and contributes to the loss of bone support generating mobility, bleeding on probing, recession and suppuration. Objective: Conduct a critical review of the literature. From the last three years, on the various treatments of surface defects affected by peri-implant disease. Methods: An electronic search was carried out with defined keywords and four databases were used, allowing the definition of the research question, together with the articles that met the inclusion and exclusion criteria established in the protocol that led to obtaining the studies considered for the study. Literary review. Likewise, the data were tabulated to carry out their proper analysis that allows answering the research question and in turn meeting the objectives formulated. Results: The mechanical debridement surgical technique is an escape procedure to eliminate microorganisms from the rough surfaces of the implants, however, this is the first option when choosing a periimplant treatment. Implantoplasty is a mechanical treatment that significantly reduces the signs associated with peri-implantitis such as BOP by decreasing PPD